Safety of HTX-019 (intravenous aprepitant) and fosaprepitant in healthy subjects. (5th June 2018) - Ottoboni, Tom; Lauw, Michael; Keller, Mary Rose; Cravets, Matt; Manhard, Kimberly; Clendeninn, Neil; Quart, Barry
Aim: Evaluate safety of HTX-019, a novel polysorbate 80– and synthetic surfactant-free intravenous formulation of neurokinin 1 receptor antagonist aprepitant for chemotherapy-induced nausea and vomiting.Methods: Two open-label, randomized, two-way crossover studies evaluated treatment-emergent adverse events (TEAEs) in 200 healthy subjects. Subjects received HTX-019 130 mg (30-min infusion) and fosaprepitant 150 mg (20- or 30-min infusion), with ≥7-day washout between doses.Results: Less than or equal to 30 min after start of infusion, TEAEs occurred in 5 (3%) HTX-019 and 30 (15%) fosaprepitant recipients. No HTX-019 recipients had infusion-site adverse events, versus 15 (8%) fosaprepitant recipients. Treatment-related dyspnea occurred in one HTX-019 and six fosaprepitant recipients. No severe/serious TEAEs occurred; all TEAEs resolved.Conclusion: HTX-019 may provide a safer aprepitant formulation than fosaprepitant for chemotherapy-induced nausea and vomiting prevention.